Nummular Dermatitis Masquerading as Recalcitrant Tinea Corporis: A Diagnostic Pitfall Resolved by Dermoscopy and Histopathology - Rina Gustia; Deasy Archika Alvares; Mutia Sari (HM Publisher, 2025)
Background: The morphological mimicry between nummular dermatitis (ND) and tinea corporis represents a significant source of diagnostic error in clinical practice. This convergence on a similar clinical phenotype—the annular plaque—often leads to inappropriate antifungal therapy and a protracted, debilitating course for the patient, as powerfully illustrated in this case. Case presentation: We present the case of a 22-year-old female with a five-year history of chronic, recalcitrant, and intensely pruritic annular plaques on her lower legs, with a baseline pruritus score of 8/10 on a Visual Analog Scale (VAS). Previous treatments based on presumptive diagnoses, including potent topical corticosteroids and systemic antifungals, had failed. This report demonstrates a pivot from a morphology-based assessment to a multimodal diagnostic algorithm. The cornerstone of this shift was dermoscopy, which revealed patchy, irregularly distributed red dotted vessels—a classic signature of an eczematous process—and a notable absence of features suggestive of a dermatophyte infection. The diagnosis was confirmed by histopathology. A strong correlation between disease flares and psychosocial stressors was identified, and a holistic management plan targeting the cutaneous inflammation, the compromised skin barrier, and the neurogenic triggers led to a rapid and substantial improvement in her clinical status and quality of life, with the Dermatology Life Quality Index (DLQI) score decreasing from 9 to 3 and the pruritus VAS score dropping to 1/10. Conclusion: This case argues for a revised diagnostic paradigm for chronic annular lesions, one that de-emphasizes ambiguous morphology and prioritizes the integration of a detailed psychodermatological history with in-vivo microscopic analysis via dermoscopy. This approach not only prevents therapeutic futility but also underscores that successful, long-term management of ND is contingent upon a patient-centered strategy that addresses the interconnectedness of the skin barrier, the immune system, and the psycho-neuro-cutaneous axis.